Gebyar Literasi Upaya Meningkatkan Kemampuan Literasi Membaca Dan Menulis Siswa SD Kelas Rendah Melalui Program Literasi Digital - Uki Hares Yulianti; Nadia Gitya Yulianita Yulianita; Lalita Melasarianti; Gita Anggria Resticka (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2025)
The basic literacy skills of lower-grade students at Kranji 4 Public Elementary School in Purwokerto remain low, with many students unable to read and write well. Despite adequate access to technology, the use of gadgets is still limited to games and is not optimal for learning. This community service program aims to improve the reading and writing skills of lower-grade elementary school students through the implementation of an innovative digital literacy program. The methods used include Focus Group Discussions (FGDs), outreach, workshops, and the application of learning technology. The program integrates the revitalization of the School Literacy Movement (GLS) with a structured schedule of 15 minutes of daily reading, followed by writing activities. The digital component includes the use of learning applications, interactive media, and educational games for English and other subjects. Teachers received workshop training to develop interactive digital learning media, while parents were actively involved in supporting literacy activities at home. The program results showed significant improvements, with 87% of students improving their reading skills and 92% of students producing written works. The program successfully produced six anthologies with ISBNs containing 156 student works. Daily GLS activities have been proven to be effective in improving vocabulary and basic literacy skills, providing a positive impact on students, teachers, and parents in understanding the importance of digital literacy as a 21st-century skill.